Study on the Gas Desorption Regularity of Coal Lumps of Different Sizes under Different Water Inundation Conditions - Wang, Ran (International Journal of Natural Resources and Environmental Studies, 2024)
Coal mining can create a large number of abandoned areas, which contain rich coalbed methane resources. The adsorption principle of the residual gas left in the abandoned coal seam is an important part of the coalbed methane resources. The adsorption principle is of great significance for the evaluation of coalbed methane resources in abandoned coal seams. However, due to the complex environment in abandoned coal seams, the factors affecting the adsorption of residual gas in abandoned coal seams are also complex. Among them, water is an important factor that affects the adsorption of residual gas in abandoned coal seams. The study on the adsorption of residual gas in abandoned coal seams with different water infiltration conditions is less. Therefore, a block coal water-flooding gas adsorption device was developed for the study of block coal gas adsorption, and the adsorption rate of block coal gas under different water infiltration conditions was determined experimentally.